Попытка преодоления традиционной концептуальной оппозиции колоративов "белый-чёрный" в художественном мире С. Есенина и А. Ахматовой - Мирошниченко, Мария Павловна (Харьковский национальный педагогический университет им. Г. С. Сковороды, 2019)
В статье исследуются колоративы "белый" и "черный" в лирике С. Есенина и А. Ахматовой, которые репрезентируют традиционную оппозицию добра и зла. В лирике поэтов присутствует как традиционная концептуализация оппозиции белое-чёрное (добро-зло), так и попытка преодоления этой традиции. Цель статьи – исследовать авторскую попытку преодоления концептуальной оппозиции белое-чёрное (добро-зло) в творчестве поэтов. В статье сделан вывод, что в сферу оппозиции "белого", т.е. духовного, и "чёрного", т.е. препятствия, входят принципиально различные образы. В лирике Есенина – это личность, смиренная душа (определяется белым цветом), которую омрачают пороки (определяется чёрным), а в лирике Ахматовой – это поэзия, любовь к мужчине и Бог (белый), которые омрачают муки творчества, трудные чувства, боль. Таким образом, в лирике С. Есенина и А. Ахматовой представлены различные пути преодоления традиционного противоречия оппозиции белое-чёрное (добро-зло), основное отличие которых заключается в том, что в герое Есенина белое находится в нём самом, а у героини Ахматовой – вне неё, или достигается благодаря чему-то, воздействующему извне.

The article examines the colorative "white" and "black" in the lyrics of S. Yesenin and A. Akhmatova, which represent the traditional opposition of good and evil. In the lyrics of the poets there is a traditional conceptualization of the opposition white-black (good-evil), and an attempt to overcome this tradition. The purpose of the article is to explore the author's attempt to overcome the conceptual opposition of white-black (good-evil) in the works of poets. The article concluded that in the sphere of opposition "white", i.e. spiritual, and "black", i.e. obstacles, are fundamentally different images. There is a person, a humble soul (defined by white), which is overshadowed by vices (determined by black) in the lyrics of Yesenin, and there are poetry, love for a man and for a God (white), which are overshadowed by the agony of creativity, difficult feelings and pain in Akhmatova’s lyrics. Thus, the lyrics of S. Yesenin and A. Akhmatova present various ways of overcoming the traditional contradiction of the opposition white-black (good-evil), the main difference of which lies in the fact that in the hero of Esenin the white is in himself, and in the heroine of Akhmatova is outside of it, or achieved through something that influences from the outside.
The attempt to overcome the traditional conceptual opposition of coloratives "white-black" in the art world S. Esenin and A. Ahmatova
Keywords: русская литература; добро; зло; прилагательные-колоративы; лирика; писатели; цветовая символика; white; black; good; evil; Yesenin; Akhmatova; overcoming a contradiction